Divergence and convergence in international regulatory policies regarding genome-edited food: How to find a middle ground - Tachikawa, Masashi; Matsuo, Makiko (Frontiers in Plant Science, 2023)
Regulations for organisms and products to which genome-editing technologies are applied are becoming even more diverse, with the path-dependent effect of previous regulations of genetically modified organisms. Regulations for genome editing technologies looks like a patchwork internationally, which will be difficult to harmonize. However, if the approaches are arranged in chronological order and the overall trend is examined, it can be seen that the regulation of genome-edited organisms and GM food products has recently been trending toward a middle ground which can be characterized as “limited convergence.” In other words, there seems to be a trend toward the adoption of two approaches: one that considers GMOs but tries to apply simplified regulations and one that excludes them from the scope of regulations as non-GMOs but requires confirmation. These two approaches are an attempt to take a middle ground between applying strict GMO regulations and excluding GMOs from the regulations as equivalent to conventional breeding. In this paper, we discuss why there is a tendency at this stage to converge on these two approaches and examine the challenges and implications of these two approaches for the governance of the agricultural and food sectors with the application of genome-editing.